DIGITAL LITERACY INITIATIVES EMPOWERING MARGINALIZED COMMUNITIES THROUGH TECHNOLOGY INTEGRATION - Prasastiningtyas, Widyapuri; Kurniawan, Aptu Andy; Ruswandi, Andi; Gymnastiar, Iman Ahmad; Amin, Fitrani (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2024)
Digital literacy initiatives are crucial in empowering marginalized communities by integrating technology into their daily lives. This study examines the effectiveness of various digital literacy programs aimed at enhancing the technological skills of marginalized groups, thereby promoting socio-economic development and inclusion. Utilizing a mixed-methods approach, this research combines quantitative surveys and qualitative interviews to assess the impact of digital literacy initiatives on participants' skills, confidence, and socio-economic status. The findings indicate significant improvements in digital competencies, which correlate with increased employment opportunities, better access to services, and enhanced community participation. Furthermore, the study highlights the challenges faced by these initiatives, including limited access to resources, technological infrastructure, and resistance to change. The research concludes with recommendations for policymakers and practitioners to improve the design and implementation of digital literacy programs, ensuring they are inclusive, sustainable, and effective in bridging the digital divide. By focusing on the transformative potential of technology integration, this study underscores the importance of digital literacy as a foundational element for achieving broader socio-economic goals.